Isomorphism Identification Among Kinematic Chains Of Group-Iv-D, E And F - Ali Hasan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The objective of this paper is to determine identification numbers of each kinematic chains of group IV-D, E, and F. This study checks the isomorphism among 10 Links, 13 Joints, Single degree of freedom Kinematic Chains of Group IV-D, E and F. The author used a Joint-Joint [JJ] matrix methodology. In this methodology, the identification numbers ‘sum of the absolute values of the characteristic polynomial coefficients’ [SCPC] and ‘maximum absolute value of the characteristic polynomial coefficient’ [MCPC] are calculated for each matrix with the help of MATLAB Identification of isomorphism in the mechanism kinematic chains. The novelty of this study is that the study may be used as guidelines for new researchers / design engineers and scientist in designing the best kinematic chain to do the pre-decided design in the initial stage of their research work. The study is explained with the help of examples of planar kinematic chain having simple joints.